Kejadian Infeksi Saluran Pernafasan Akut (ISPA) Pada Balita Di Puskesmas Pusako Kabupaten Siak - Yulia Riza; Mitra; Hendri (Sistem Informasi, 2023)
The efforts to eradicate Diseases Control for Acute Respiratory Infection (DC-ARI) Program's in toddlers, namely the need for steps to carry out promotion of Acute Respiratory Infection (ARI) prevention, find patients, carry out standard management of patients with early detection, appropriate and immediate treatment, and carry out supervision and control of morbidity and mortality due to ARI. The purpose of this study was to determine the incidence of acute respiratory infection (ARI) in toddlers at the Pusako Health Center Work Area, Siak Regency. The research method is qualitative with Rapid Assessment Procedure design, interviews were conducted using purposive sampling technique and observation of service implementation and recording of DC-ARI program report. The results showed that the DC-ARI program was still not optimal because the program holders had not received training, and due to the covid-19 pandemic, health workers were unable to pick up the ball to handle ARI in toddlers, lack of synergy from the community and public figure to participate in reducing ARI cases in toddlers at the Pusako Health Center. It can be concluded that there needs to be a plan made by the person in charge of DC-ARI so that the target of ARI in toddlers is decreased, there must be continuity and public awareness of the importance of knowing ARI disease in toddlers through counseling and socialization provided by the health promotion so that DC-ARI activities can be optimal.